Addressing Gender Gaps in the Ugandan Labor Market - Kasirye, Ibrahim (Economic Policy Research Centre, 2011)
Four out of every five women in Uganda are employed in agriculture, according to the 2008 Gender and Productivity Survey (GPS) in Uganda (EPRC, 2009); and 42 percent of women in the labour force are unpaid family workers—receiving no income despite contributing the largest proportion of the agricultural labour. Gender discrimination in the labour market is a pervasive economic problem in developing countries.1 Discrimination based on sex can take many forms in the labour market—from restricted access to certain sectors of employment—to differential pay by gender. As earlier noted, whereas 42 percent of women in Uganda are unpaid family workers, the corresponding rate for men is only 16 percent according to the 2008 GPS. Furthermore, the 2008 GPS shows that in the private sector, women in Uganda receive on average lower pay than men. Gender gaps in the labour market do not only lead to reduced incomes for women but also affects the status of women within society. Nevertheless, gender norms continue to dictate what a woman can and cannot do in Uganda and whether she can work outside her marital home. This environment has ensured that female exploitation in the labour market persists. As such, there is a need to address gender equity in labour market in Uganda—especially as the country attempts to attain the Millennium Development Goals (MDGs).